2020
DOI: 10.1002/jbm.a.37001
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of multiscale anisotropic hydrogels through interfacial polyionic complexation

Abstract: Polysaccharides are explored for various tissue engineering applications due to their inherent cytocompatibility and ability to form bulk hydrogels. However, bulk hydrogels offer poor control over their microarchitecture and multiscale hierarchy, parameters important to recreate extracellular matrix-mimetic microenvironment. Here, we developed a versatile platform technology to self-assemble oppositely charged polysaccharides into multiscale fibrous hydrogels with controlled anisotropic microarchitecture. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Moreover, the RegenMatrix hydrogel used in this study showed 674.3% (±103.4) elongation and 29.6 (±11.8) kJ/m 3 toughness when tested as a bilayer film in our previous study. 14 Swelling studies of the bilayer film hydrogels showed 417.5% (±125.4) equilibrium swelling compared to dry bilayer films (data not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, the RegenMatrix hydrogel used in this study showed 674.3% (±103.4) elongation and 29.6 (±11.8) kJ/m 3 toughness when tested as a bilayer film in our previous study. 14 Swelling studies of the bilayer film hydrogels showed 417.5% (±125.4) equilibrium swelling compared to dry bilayer films (data not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…CHT (1% w/v) and KCA (1% w/v) solutions showed +82 (±4.78) and negative −79.5 (±4.21) zeta potential as reported in our previous study. 14 Two programmable syringe pumps (BS300, Braintree Scientific INC., Braintree, MA) were used at a speed of 50 mL/h. Each pump held CHT (1% w/v) and KCA (1% w/v) solutions in separate 10 mL plastic syringes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interfacial polyionic complexation of oppositely charged polysaccharide pairs (i.e., positively charged CS with negatively charged κ-carr, alginate, or gellan gum) was used to produce continuous interfacial fibers with strong mechanical properties [269]. These bioinspired hydrogels presented multiscale hierarchy (parallel or perpendicular align-ment), ability to encapsulate NPs, small molecules or to form composites with other macromolecules [270,271].…”
Section: Other Polyssacharidesmentioning
confidence: 99%